PENGARUH KEPADATAN TERNA DAN LAMA PENYULINGAN TERHADAP RENDEMEN DAN KARAKTERISTIK MINYAK Melaleuca bracteata - NANAN NURDJANNAH (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
The influence of material bulk density and duration of distillation on the yi eld and characteristic of Melaleuca bracteata oilMelaleuca bracteata belongs to Myrtaceae family which is grown wildly in Australia and Quensland. The oil is produced from Ihe leaves and (wigs by distillation and is used in fragrances industry. The oil content of leaves and twigs range between 0.4 to 1.0% with metil eugenol as the major component (70-80%). Because of its high metil eugenol content M. bracteata oil can be used to control fruil flies The experiment was carried out to evaluate the influence of material bulk density in the distillation vessel and duration of distillation on the yield and charac¬ teristic of the oil produced. Material used was (he leaves and twigs of M bracteata from the experimental garden of the Research Institute for Spice and Medicinal Crops. Manoko, Lembang (1200 in above the sea level). The experiment at 1993 was designed as completely randomized design, arranged factorially with three replications. The result showed that the optimum distillation condition was 1 56 g/l material bulk density in the vessel and 3 hours distillation. Such distillation condition produced 1.09 % oil yield with (he characteristics as follow speciic gravity I 0263, refractive index 1 5296, optical rotation -3.3°, solubility in 70% cthanol 1 : 1, methyl eugenol content 86.1%, acid number 0.56, ester number 15.4 and ester number after acetylation 39.3. Referring to Australia oil, the Indonesian M bracteata oil has higher value of esther number both before and after acetylation.